Simulation-based education improves military trainees' skill performance and self-confidence in tourniquet placement: A randomized controlled trial. (23rd August 2022) - Scalese, Ross J.; Issenberg, S. Barry; Hackett, Matthew; Rodriguez, Richard D.; Brotons, Angel A.; Gonzalez, Marco; Geracci, James J.; Schulman, Carl I.
Abstract : This randomized controlled educational trial demonstrated that a focused simulation-based TCCC training intervention resulted in significant improvements in military trainees' skill performance and self-confidence in tourniquet placement. Abstract : BACKGROUND: Tactical Combat Casualty Care (TCCC) is the standard of care for stabilization and treatment of military trauma patients. The Department of Defense has mandated that all service members receive role-based TCCC training and certification. Simulation education can increase procedural skills by providing opportunities for deliberate practice in safe, controlled environments. We developed and evaluated the effectiveness of a simulation-based TCCC training intervention to improve participants' skill performance and self-confidence in tourniquet placement. METHODS: This study was a single-blinded, randomized trial with waitlist controls. Army Reserve Officers Training Corp cadets from a single training battalion comprised the study population. After randomization and baseline assessment of all participants, group A alone received focused, simulation-based TCCC tourniquet application training. Three months later, all participants underwent repeat testing, and after crossover, the waitlist group B received the same intervention. Two months later, all cadets underwent a third/final assessment. The primary outcome was tourniquet placement proficiency assessed by total score achieved on a standardized eight-item skill checklist. A secondary outcome was self-confidence in tourniquet application skill as judged by participants' Likert scale ratings. RESULTS: Forty-three Army Reserve Officers Training Corp cadets completed the study protocol. Participants in both group A (n = 25) and group B (n = 18) demonstrated significantly higher performance from baseline to final assessment at 5 months and 2 months, respectively, following the intervention. Mean total checklist score of the entire study cohort increased significantly from 5.53 (SD = 2.00) at baseline to 7.56 (SD = 1.08) at time 3, a gain of 36.7% ( p < 0.001). Both groups rated their self-confidence in tourniquet placement significantly higher following the training. CONCLUSION: A simulation-based TCCC curriculum resulted in significant, consistent, and sustained improvement in participants' skill proficiency and self-confidence in tourniquet placement. Participants maintained these gains 2 months to 5 months after initial training. LEVEL OF EVIDENCE: Therapeutic/care management; Level II. Abstract :